AUDIOMETRIC CHANGES IN PATIENTS WITH TYPE 1 DIABETES MELLITUS (World Bulletin of Public Health, 2023)
One of the important problems of modern otorhinolaryngology in medical and social aspects is the diagnosis and treatment of sensorineural hearing loss and vestibular disorders. Every year in Russia, thousands of children are identified with damage to the auditory system, and this trend has a clearly progressive nature (Daikhes N.A. et al., 2018; Tavartkiladze G.A. 2016). Hearing loss is of particular importance, since hearing pathology causes disturbances in the child’s mental and speech development, as well as in the child’s further socialization. The most pronounced cochleo-vestibular syndrome appears with a combined pathology of the inner ear and etiopathogenetically similar diseases with pronounced pathogenetic processes. One of these diseases is type 1 diabetes. In the pathogenesis of sensorineural disorders, equally as in diabetes mellitus, the main link is a violation of microcirculation, tissue hypoxia, an imbalance of redox processes, etc. Ischemic processes can manifest themselves at the level of the receptor apparatus of the inner ear, conduction tracts, auditory and vestibular nuclei medulla oblongata and cortical structures.
Keywords: sensorineural; vestibular; audiometry